Factors Related to Alcohol Consumption Among Japanese Physicians. (April 2018) - Ohida, Noriyasu; Otsuka, Yuichiro; Kaneita, Yoshitaka; Nakagome, Sachi; Jike, Maki; Itani, Osamu; Ohida, Takashi
This study aimed to investigate the drinking habits of Japanese physicians, and clarify their causal factors. A self-administered questionnaire was sent to 6000 male and 1500 female physicians, selected from among members of the Japan Medical Association. We analyzed the correlation of drinking habits with age, medical department, smoking and exercise status, work environment, sleep problems, and mental health. The response rate was 79.4%. Physicians with a heavy drinking habit were most frequently men in their 60s and women in their 20s to 50s. Drinking or heavy drinking tendencies decreased with increasing age. Smoking status was correlated with heavy drinking. Exercise status was correlated with drinking among men, and drinking/heavy drinking among women. Mental health was not correlated with drinking habit. However, sleep problems were correlated with a heavy drinking habit. These results suggest that countermeasures need to be taken to decrease the rate of heavy drinking among physicians.